ANALISIS STRATEGI PEMASARAN EKOWISATA MENGGUNAKAN METODE SWOT DAN QSPM - Muhammad Harisudin; Qurtubi Qurtubi (Jurnal Disprotek, 2023)
The Special Region of Yogyakarta has a wealth of potential natural resources that can be used as capital to develop the tourism industry by utilizing natural potential. One of the nature-based tourism developed in Indonesia is Ecotourism, located on Jalan Kaliurang. The growing proliferation of nature-based tourism is one of the challenges for the Ecotourism manager because there are more and more competitors. So the purpose of this research is to determine the right marketing strategy to be implemented by the Ecotourism manager. This research is expected to positively impact the development of Ecotourism so that more and more tourists come to visit, which will improve the Meconomy of the community around Ecotourism. Data collection methods used are interviews and observation. The data analysis method used is SWOT analysis and quantitative strategic planning matrix method. The data processing results using SWOT analysis show that Ecotourism is in a "strong" and "opportunistic" position. The alternative strategy recommended is to create better branding regarding Ecotourism products and services to both visitors and stakeholders and maintain the sustainability of Ecotourism by managing products, customers, stakeholders, and society. In comparison, the results of the QSPM method produce a recommended strategy to be carried out by the Ecotourism manager, namely maintaining Ecotourism's sustainability by managing products, customers, stakeholders, and society.